A new parameter for the determination of normal right ventricular function in patients with acute pulmonary embolism - Kerkütlüoğlu, Murat; Güneş, Hakan; Yücel, Oguzhan; Doğan, Ömer; Yılmaz, Mehmet Birhan (Journal of Surgery and Medicine, 2021)
Background/Aim: The performance of the right ventricular myocardium is crucial in various pathological states and the right ventricular dysfunction has a prognostic value in pulmonary embolism. We sought to bring out which parameters were helpful in predicting a normal right ventricular function in patients with acute pulmonary embolism. Methods: Consecutive 100 acute pulmonary embolism patients, who were hospitalized and confirmed by computed tomography angiography, were enrolled in this cohort study. All patients’ demographics, symptoms on admission, risk factors, electrocardiography and laboratory findings, and hemodynamic parameters were assessed. Echocardiography was performed in the first 24 hours. The study group of pulmonary embolism patients was divided into two groups based on their basic characteristics: Patients with normal right ventricular function and patients with right ventricular failure. Results: The average age of the patients was 63 (16) years, with 48 (48%) of them being male. Twenty three patients (23%) had normal RV functions. According to the multiple logistic regression analysis, age (P=0.041, OR: 1.174, 95% CI: 1.007 to 1.368), oxygen saturation (P=0.026, OR: 1.372, 95% CI: 1.039 to 1.812) and heart rate (P=0.049, OR: 1.160, 95% CI: 1.001 to 1.346) were independent predictors of normal RV function. The setting in which all three parameters (Age, Heart rate, Oxygen saturation) were positive was considered AHO index=1, with a positive predictive value of 100% a sensitivity of 44%, a negative predictive value of 85.6% and a specificity of 100% (AUC: 0.717, 95% CI: 0.619 to 0.803) for normal RV function. Conclusion: In acute pulmonary embolism patients who were younger than 53 years of age with a heart rate of ≤118 bpm and an oxygen saturation of >90% (AHO index=1), right ventricular functions were normal. Accordingly, without the need of computed tomography angiography or echocardiography, the clinician may predict normal right ventricular function with available demographic and noninvasive hemodynamic parameters.